###### Advertisements

###### Advertisements

Sum

**Evaluate: **xz (x^{2} + y^{2}) for x = 2, y = 1 and z= 1.

###### Advertisements

#### Solution

For x = 2, y = 1 and z = 1

xz (x^{2} + y^{2})

2(1) × (2^{2} + 1^{2})

2 × (4 + 1)

2 × 5

= 10

Concept: Multiplying a Polynomial by a Polynomial

Is there an error in this question or solution?

#### APPEARS IN

#### RELATED QUESTIONS

**Multiply:** 6x^{3} − 5x + 10 by 4 − 3x^{2}

**Multiply: **2y − 4y^{3} + 6y^{5} by y^{2} + y − 3

**Simplify : **(4x – 5y) (5x – 4y)

The base and the altitude of a triangle are (3x – 4y) and (6x + 5y) respectively. Find its area.

Multiply -4xy^{3} and 6x^{2}y and verify your result for x = 2 and y= 1.

Evaluate (3x^{4}y^{2}) (2x^{2}y^{3}) for x = 1 and y = 2.

If x = 2 and y = 1; find the value of (−4x^{2}y^{3}) × (−5x^{2}y^{5}).

**Evaluate: **(2x – 5y)(2x + 3y) for x = 2 and y = 3.

**Evaluate: **2x(3x – 5) – 5(x – 2) – 18 for x = 2.

**Multiply and then verify :**

−3x^{2}y^{2} and (x – 2y) for x = 1 and y = 2.